Extensive reading: The vocabulary levels of English-subtitled Korean, Japanese and Chinese drama series - Hsu, Wenhua (English Language Teaching Educational Journal, 2023)
‘Drama fever’ has been riding high with increasing consumer usage of OTT streaming services and prevalence of Internet-connected mobile devices, leading to the phenomenon of binge-watching on college campuses in Taiwan. This study targeted English subtitles as a source of input, since they offer EFL leaners a channel for exposure to English. The researcher compiled four corpora with each having approximately 2.5 million English-subtitled words from Korean, Japanese, American and Chinese TV series across a couple of genres with high viewership ratings on OTT services for comparison. The operational measures involved vocabulary levels along the word-frequency scale of the British National Corpus and the Corpus of Contemporary American English. Results showed that English-subtitled Korean, Japanese and Chinese dramas reached the 2nd—3rd 1000 word-family levels at 95% text coverage and the 4th—5th 1000 levels at 98% coverage, while American series extended to the 7th—8th 1000 levels at 98% coverage from the 3rd—4th 1000 levels at 95% coverage. The data may serve as a reference concerning the vocabulary goal within the first 5000 word families for EFL learners if they continually binge-watch drama series at their leisure time.